Microbial community diversity of an integrated constructed wetland used for treatment of sewage - Seth, Nidhi; Vats, Sharad; Lakhanpaul, Suman; Arafat, Yasir; Mazumdar-Leighton, Sudeshna; Bansal, Mansi; Babu, C. R. (Frontiers in Microbiology, 2024)
The microbial community diversity in Constructed Wetland System (CWS) plays a key role in the removal of pollutants from waste water. An integrated functional CWS developed at Neela Hauz Biodiversity Park, Delhi was selected to assess the diversity in composition and structure of microbial community diversity of sludge and sediment of CWS, based on metagenomic approach using 16S rRNA genes. The sediment showed higher diversity than sludge and both formed distinct clusters. The taxonomic structure of the microbial community of CWS is represented by 6731 OTUs distributed among 2 kingdoms, 103 phyla, 227 classes, 337 orders, 320 families, 295 identified genera and 84 identified species. The relative abundance of top 5 dominant phyla of sludge and sediment varied from 3.77% (Acidobacteria) to 35.33% (Proteobacteria) and 4.07% (Firmicutes) to 28.20% (Proteobacteria), respectively. The range of variation in relative abundance of top 5 dominant genera of sludge and sediment was 2.58% (Hyphomicrobium) to 6.61% (Planctomyces) and 2.47% (Clostridium) to 4.22% (Syntrophobacter), respectively. The rich microbial diversity of CWS makes it perform better in pollutants removal (59.91% to 95.76%) than other CWs. Based on the abundance values of taxa, the taxa are grouped under four frequency distribution classes − abundant (>20), common (10-19), rare (5-9) and very rare (1-4). The unique structure of microbial communities of integrated CWS is that the number of abundant taxa decreases in descending order of taxonomic hierarchy, while the number of rare and very rare taxa increases. For example, the number of abundant phyla was 14 and 21 in sludge and sediment, respectively and both communities have only 3 abundant genera each. This is in contrast to 4 and 17 very rare phyla in sludge and sediment, respectively and both the communities have 114 and 91 very rare genera, respectively. The outcomes of the study is that the integrated CWS has much higher microbial community diversity than the diversity reported for other CWs, and the rich diversity can be used for optimizing the performance efficiency of CWS in the removal of pollutants from waste water. Such structural diversity might be an adaptation to heterogeneous environment of CWS.